2018
DOI: 10.1038/gim.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

B3GAT3-related disorder with craniosynostosis and bone fragility due to a unique mutation

Abstract: All sequenced patients showed a unique homozygous mutation of c.667G>A, p.Gly223Ser (NM_012200) in the beta-1,3-glucuronyltransferase 3 (B3GAT3) gene known to be involved in linkeropathy syndrome. Linkeropathies correspond to a recently identified group of heterogeneous genetic syndromes along a spectrum of skeletal and connective tissue disorders. These patients featured mainly craniosynostosis, midface hypoplasia, bilateral radioulnar synostosis, multiple neonatal fractures, dislocated joints, joint contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Because the patient's phenotype was more severe than that reported for other patients with mutations in B3GAT3, the authors performed exome sequencing, but did not find any additional causative mutation [73]. Similar features with bone fragility and severe osteopenia have been reported recently by Yauy et al [74]. Alazami et al reported a gerodermia osteodysplastica-like phenotype in a patient with a homozygous missense mutation in B3GAT3 (c.245C>T, p.Pro82Leu) [75].…”
Section: Disorders Linked To Proteins Involved In the Synthesis Of Thmentioning
confidence: 57%
See 1 more Smart Citation
“…Because the patient's phenotype was more severe than that reported for other patients with mutations in B3GAT3, the authors performed exome sequencing, but did not find any additional causative mutation [73]. Similar features with bone fragility and severe osteopenia have been reported recently by Yauy et al [74]. Alazami et al reported a gerodermia osteodysplastica-like phenotype in a patient with a homozygous missense mutation in B3GAT3 (c.245C>T, p.Pro82Leu) [75].…”
Section: Disorders Linked To Proteins Involved In the Synthesis Of Thmentioning
confidence: 57%
“…Similar features with bone fragility and severe osteopenia have been reported recently by Yauy et al . . Alazami et al .…”
Section: Glycosaminoglycan Chain Synthesis‐related Disordersmentioning
confidence: 99%
“…In 6 patients from 4 unrelated consanguineous families, a unique homozygous mutation in the B3GAT3 gene was identified [Yauy et al, 2018]. During the prenatal period, Antley-Bixler syndrome was clinically suspected [Yauy et al, 2018].…”
Section: B3gat3mentioning
confidence: 99%
“…During the prenatal period, Antley-Bixler syndrome was clinically suspected [Yauy et al, 2018]. The patients had craniosynostosis, midface hypoplasia, bilateral radioulnar synostosis, multiple neonatal fractures, dislocated joints, joint contracture, long fingers, foot deformities, and cardiovascular abnormalities [Yauy et al, 2018].…”
Section: B3gat3mentioning
confidence: 99%
See 1 more Smart Citation